Qualitative Study: The Diffusion Innovation Theory to Long Term Reversible Contraception Method Selection in High Risk Women, Malang District - Linda R Wati; Kunawati T Dewi; Erdiana D Putri (Journal of Midwifery, 2021)
Research objective: Long-term reversible contraceptive method (LTRC) is the most effective form of contraception but women prefer lesser effective method. In this study we explored whether women of reproductive age will accept or reject LTRC as their contraceptive innovation, and how their perceptions on the innovation's attributes influence their decision in choosing LTRC.Design, participants, interventions, and outcomes: The research design used was a qualitative descriptive study with high-risk reproductive women who were over 35 years old (16 people) spread over 4 health centers (puskesmas) as participants. Data collection was done by using focus group discussion. The results were analyzed using thematic content analysis.Result: Data analysis revealed that there were 2 subgroups of participants based on their tendency to use LTRC: positive (n 6) and negative (n 10). Most of the participants were aware of the advantages of long-term reversible contraceptive methods. They get information from health workers, the media and other people's experiences. They think that both IUD and implants have a high complexity / difficulty, especially the IUD.   The characteristics of innovation in the form of relative advantage, compatibility, complexity, trialability and ease of observation greatly influence the decision to choose a long-term reversible contraceptive method. Most of the participants refused to try using the LTRC because it was too risky to try and too complicated to use.Conclusion: Most women are still hesitant to choose LTRC as a contraceptive, especially intrauterine contraceptives. They need more information about the advantages of LTRC